Evaluation of a large dish-type concentrator solar lighting system for underground car park - Song, Duofu; Lv, Hui; Liao, Jun; Huang, Wenjuan; Huang, Sihao; Cheng, Chunfu; Zhou, Huiliang; Su, Yuehong; Riffat, Saffa (Wiley, 2018)
To utilize solar energy more efficiently and reduce lighting power consumption in underground public spaces such as car park, a large dish-type concentrator solar lighting system is put forward along with its evaluation, which is a unique design to apply a laminated layer of beam split thin film coating and thin film solar cells onto the dish reflector. The collected sunlight is split into two parts, one being reflected into a fibre optical bundle (FOB) and transmitted for daylighting while the rest being absorbed by solar cells for electricity generation as other way to replenish daylighting. A set of four solar lighting system using 3.28m diameter dish are designed to meet the lighting requirement in a 17712munderground car park. A mathematical model is adopted to calculate the output power and conversion efficiency of solar cells distributed on the parabolic dish surface. The indoor illuminance distribution is given by lighting simulation. The results indicate that the average daylight illuminance in the car park can vary between 62.7 lx and 284 lx on 25 February 2016, and between 62.7 lx and 353 lx on 17 August 2016 for two chosen days respectively. For the presented design, the electricity produced by solar cells is just enough to power light emitting diodes (LEDs) for lighting meeting a criterion at night. Considering about 19% conversion efficiency of solar cells and the efficacy of 129.5 lm/W of LEDs, the hybrid solar lighting system can have about 40% utilization ratio of solar energy, so it can be concluded that a sufficient lighting provision can be provided by the proposed large dish-type concentrator solar lighting system for applications in underground car park.